Tax Payers’ Attitudes and Demographic Analysis of SMEs Operators in River and Akwa-Iboms States – Nigeria - Sunny Biobele Beredugo; Bassey Okon Ekpo (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
The study focused on taxpayers’ attitude and demographic analyses of SMEs operators in Rivers and Akwa-Ibom States – Nigeria. It was motivated by the need for Nigerian tax authority to create a well-planned and comprehensive approach to enhance favourable tax attitude in order to deal with the problem of tax evasion; coupled with the lag in sufficient empirical works on tax payers’ attitudes in Nigeria.The objectives of the study were to examine the differential effect of gender, age differences, marital status and educational level on tax payers’ attitudes in Nigeria. Survey research design was adopted. The study was limited to SMEs operators in Rivers and Akwa-Ibom States. From a population of 28,585 SMEs operators, a sample size of 1150 was used. ANOVA was used to test the hypothesis. The findings show that: there is no significant difference on the effect of genders, age differences and marital status on tax payers’ attitudes in Nigeria. However, there is a significant difference on the effect of educational level on tax payers’ attitudes in Nigeria. It was therefore recommended that tax authority should always consider the educational stratification of SMEs operators before developing approaches to instigate favourable tax compliance; and SMEs Operators with high compliance track records should be celebrated by tax authority and they should be encouraged to engage in word-of-mouth communication to communicate to others on the benefits of tax payment